Education and the historic environment - Henson, Donald; Stone, Peter G., 1957-; Corbishley, Mike (Issues in heritage management., 2004)
Practical, inspiring and instructive, Education and the Historic Environment emphasizes the contribution to both education and heritage that results from a positive relationship between the two disciplines. Education and the Historic Environment examines evidence, case studies and chapters from a wide cross section of the heritage sector and:argues for the value of using the physical remains of the pastshows how and where the historic environment can be used to fit into and enhance learningexamines how guidelines are reinforced.